1997
DOI: 10.1128/jb.179.3.928-940.1997
|View full text |Cite
|
Sign up to set email alerts
|

Propionate catabolism in Salmonella typhimurium LT2: two divergently transcribed units comprise the prp locus at 8.5 centisomes, prpR encodes a member of the sigma-54 family of activators, and the prpBCDE genes constitute an operon

Abstract: We present the initial genetic and biochemical characterization of the propionate (prp) locus at 8.5 centisomes of the Salmonella typhimurium LT2 chromosome (T. A. Hammelman et al., FEMS Microbiol. Lett. 137: 233-239, 1996). In this paper, we report the nucleotide sequences of two divergently transcribed transcriptional units. One unit is comprised of the prpR gene (1,626 bp) encoding a member of the sigma-54 family of transcriptional activators; the second unit contains an operon of four genes designated prpB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
124
0
3

Year Published

1999
1999
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(128 citation statements)
references
References 40 publications
1
124
0
3
Order By: Relevance
“…the acetate kinase (AckA) and phosphotransacetylase (Pta) pathway, and the acetyl-CoA synthetase (Acs) pathway. In a previous paper, we proposed that PrpE catalysed the synthesis of propionyl-CoA during propionate breakdown (Horswill & Escalante-Semerena, 1997). However, no evidence to support this hypothesis was presented.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…the acetate kinase (AckA) and phosphotransacetylase (Pta) pathway, and the acetyl-CoA synthetase (Acs) pathway. In a previous paper, we proposed that PrpE catalysed the synthesis of propionyl-CoA during propionate breakdown (Horswill & Escalante-Semerena, 1997). However, no evidence to support this hypothesis was presented.…”
Section: Introductionmentioning
confidence: 82%
“…The activation of propionate to propionyl-CoA is the proposed first step of the methylcitric acid cycle and of all other propionate breakdown pathways in bacteria (Horswill & Escalante-Semerena, 1997 ;Textor et a/., 1997). However, no evidence has been reported identiAbbreviations: Ap, ampicillin; Cm, chloramphenicol; Km, kanamycin; Tc, tetracycline.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, propionaldehyde is converted to propanol and propionate by alcohol dehydrogenase, CoA-dependent propionaldehyde dehydrogenase, phosphotransacylase and propionate kinase (Obradors et al, 1988;Toraya et al, 1979). This pathway generates one ATP, an electron sink for the regeneration of NAD and an intermediate (propionyl-CoA) that can serve as a carbon and energy source via the methylcitrate pathway (Horswill & Escalante-Semerena, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, propionaldehyde is converted to propanol and propionate by alcohol dehydrogenase, CoA-dependent propionaldehyde dehydrogenase, phosphotransacylase and propionate kinase (Obradors et al, 1988;Toraya et al, 1979). This pathway generates one ATP, an electron sink for the regeneration of NAD and an intermediate (propionyl-CoA) that can serve as a carbon and energy source via the methylcitrate pathway (Horswill & Escalante-Semerena, 1997).Although the pathway of 1,2-PD degradation appears quite straightforward, the catabolism of this small molecule is in fact a very elaborate process (Bobik et al, 1999;Havemann et al, 2002;Havemann & Bobik, 2003). Recent studies have shown that a polyhedral body is involved in AdoCbl-dependent 1,2-PD degradation by S. enterica (Bobik et al, 1999;Havemann et al, 2002;Havemann & Bobik, 2003).…”
mentioning
confidence: 99%